2023
DOI: 10.3389/fpubh.2023.1069906
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor particulate matter exposure affects metabolome in chronic obstructive pulmonary disease: Preliminary study

Abstract: IntroductionThe metabolomic changes caused by airborne fine particulate matter (PM2.5) exposure in patients with chronic obstructive pulmonary disease (COPD) remain unclear. The aim of this study was to determine whether it is possible to predict PM2.5-induced acute exacerbation of COPD (AECOPD) using metabolic markers.MethodsThirty-eight patients with COPD diagnosed by the 2018 Global Initiative for Obstructive Lung Disease were selected and divided into high exposure and low exposure groups. Questionnaire da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…This study identified abnormalities in the metabolism of 9 glycerophospholipid species, indicating that PM2.5 may affect chicken immune responses by damaging the membrane structure of chicken cells. Under conditions of exposure to PM2.5, animals exhibit abnormal glycerophospholipid metabolism, highlighting the crucial role of glycerophospholipid metabolism in the mechanisms of PM2.5-induced damage ( Li et al, 2019 ; Yu et al, 2023 ). Steroid hormones play regulatory roles in metabolism, cell proliferation, and differentiation within the body ( Amanatullah et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study identified abnormalities in the metabolism of 9 glycerophospholipid species, indicating that PM2.5 may affect chicken immune responses by damaging the membrane structure of chicken cells. Under conditions of exposure to PM2.5, animals exhibit abnormal glycerophospholipid metabolism, highlighting the crucial role of glycerophospholipid metabolism in the mechanisms of PM2.5-induced damage ( Li et al, 2019 ; Yu et al, 2023 ). Steroid hormones play regulatory roles in metabolism, cell proliferation, and differentiation within the body ( Amanatullah et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%